Академік М.М. Гришко – основоположник наукової селекції конопель (до 115-річчя з дня народження) - Вировець, В.Г.; Лайко, І.М.; Горшкова, Л.М.; Кириченко, Г.І. (Фактори експериментальної еволюції організмів, 2016)
Aim. In the row of prominent scientists of Ukraine the eccentric figure of Mykola Hryshko is brightly distinguished, as a continuer of development of theoretical and decision of practical problems of genetics, selection and acclimatization. Methods. A talented researcher and experimenter, theorist and science propagandist began his activity with hemp, considerably deepening studies about the evolution of sex of higher plants. Results. M. Hryshko the first undertook practical steps in the decision of problem of mechanization of processes of hemp harvesting by creation of simultaneously ripening varieties. On the basis of study of nature of sex of plants and analyses of many hybrids between different sexual types the special methodology was worked out by him. After the first variety of simultaneously ripening hemp OSO72, monecious hemp with the simultaneous placing on one plant of the spatially separated female and male flowers was created by his students. Thus M. Hryshko belongs priority in the study of problem of sex of hemp. Conclusions. Begun researches of acad. M. Hryshko of the selection of hemp found the deserving continuation in the same ancient Hlukhiv the scientists of next generations as new high-performance dioecious and monoecious varieties on the example of that a myth is blown about their drug content. During all life the acad. M. Hryshko conducted the titanic advanced and organizational study. Keywords: M. Hryshko, types, varieties, dioecious and monoecious hemp, sex.